2021
DOI: 10.1038/s41467-021-25264-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously enhancing the ultimate strength and ductility of high-entropy alloys via short-range ordering

Abstract: Simultaneously enhancing strength and ductility of metals and alloys has been a tremendous challenge. Here, we investigate a CoCuFeNiPd high-entropy alloy (HEA), using a combination of Monte Carlo method, molecular dynamic simulation, and density-functional theory calculation. Our results show that this HEA is energetically favorable to undergo short-range ordering (SRO), and the SRO leads to a pseudo-composite microstructure, which surprisingly enhances both the ultimate strength and ductility. The SRO-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(57 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…In this case, the spring exhibits a maximum tensile force, similar to the ultimate tensile strength in the stress‐strain curve for elastic materials. [ 27 ] To explain the divergent spring behaviors for different‐sized patterns, we investigate the origin of the tensile force generated by the droplet‐based spring. The tensile force is the sum of the Laplace pressure F L (related to the droplet‐solid contact area and the contact angle) and the surface tension F S (related to the length of the TCL and the contact angle), [ 28 ] and the latter is dominant.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the spring exhibits a maximum tensile force, similar to the ultimate tensile strength in the stress‐strain curve for elastic materials. [ 27 ] To explain the divergent spring behaviors for different‐sized patterns, we investigate the origin of the tensile force generated by the droplet‐based spring. The tensile force is the sum of the Laplace pressure F L (related to the droplet‐solid contact area and the contact angle) and the surface tension F S (related to the length of the TCL and the contact angle), [ 28 ] and the latter is dominant.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Particularly, several recent works have demonstrated that chemical short-range order at a nanometer scale can be created in the HEAs and medium-entropy alloys, which could significantly strengthen their mechanical properties. [14][15][16] However, these research efforts have been mainly focused on the fabrication of bulk HEAs as the structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Here we prepared ferroelastic Zr x Y (1‐ x )/4 Yb (1‐ x )/4 Ta (1‐ x )/4 Nb (1‐ x )/4 O 2 ( x = 0.312 and 0.668) HEOs by the conventional solid‐state reaction method and employed a hybrid MD and Monte Carlo (MC) method as MC is more effective to optimize the random exchange atom occupancy for randomly doped high‐entropy systems 37 . Results show the ferroelastic HEOs present glass‐like low‐ k approaching the amorphous limit ( k min ), which originates from the dominant delocalized phonon modes caused by the disordered interatomic bonding force.…”
Section: Introductionmentioning
confidence: 99%